INCORPORATING PUBLIC INPUT WITH GEOGRAPHIC INFORMATION SYSTEM (GIS) FOR BICYCLE STRATEGIC PLANNING - Li, Jianling; Sin, June Chae-Un (Jurnal Perencanaan Wilayah dan Kota, 2019)
ABSTRACTDesire for active transportation is on the rise.  However, the need for data and ways to incorporate public input in bicycle strategic planning are challenges faced by local governments with inadequate resources and time.   This paper presents a case study of bicycle strategic planning in the City of Grand Prairie, Texas. It illustrates how local governments can engage the public in bicycle planning through a public input process and use of GIS.  The approach is useful for local governments elsewhere to meet their immediate needs for data and to promote active transportation with limited resources and time.